2011
DOI: 10.21608/jpp.2011.85575
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF TEMPERATURE, HUMIDITY AND WIND SPEED ON SEED SETTING AND FERTILITY OF FIVE EGYPTIAN CLOVER (Trifolium alexandrinum, L.) CULTIVARS

Abstract: Five Egyptian clover cultivars were evaluated for the fertility traits, open pollinated seed set/ floret%, no. of floret/ inflorescence. no. of inflorescences/ plant, the weight (gm) of 1000 seeds, productivity of seed per m 2 and vital pollen grain under different heat treatments o C, relative humidity % and wind speed m/sec, for four blooming periods. The study was conducted in Randomize Complete Block Design with three replications at Agricultural Research Center (ARC) in Giza Station during winter 2008-200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…1) were unfavourable for pollination resulting in a significant reduction in seed yields of cutting treatments T3 and T4 (Table 1) compared to T2 when environmental conditions were more favourable for pollination. These findings were in line with the studies that reported temperatures of 28-32 °C with a relative humidity of 45-55%, which were favourable for maximum pollination in berseem clover crops 32,33 . The timing of the last forage cut prior to seed harvesting can also impact on the efficiency of pollinators, namely honeybees.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1) were unfavourable for pollination resulting in a significant reduction in seed yields of cutting treatments T3 and T4 (Table 1) compared to T2 when environmental conditions were more favourable for pollination. These findings were in line with the studies that reported temperatures of 28-32 °C with a relative humidity of 45-55%, which were favourable for maximum pollination in berseem clover crops 32,33 . The timing of the last forage cut prior to seed harvesting can also impact on the efficiency of pollinators, namely honeybees.…”
Section: Discussionsupporting
confidence: 92%
“…The Agaitti Berseem-2002 variety performed well for both seed and forage production and so is likely to be favoured by farmers. Selection of genotypes with early seed set were favourable for high temperature and low relative humidity areas 33 . These were linked with the regulation of the movement of pollinators, which set the genotypes for early blooming and high pollination efficiency and thus increased seed yield of berseem clover.…”
Section: On-farm Evaluation Of Recommended Variety and Cutting Practimentioning
confidence: 99%
“…1). The synchronization of pollination and fertilization time with hot air temperature, low humidity, and hot desiccating winds can severely reduce seed settings in Berseem clover, as reported in several studies (El-Naby et al, 2011;El-Naby et al, 2012). Factors contributing to low seed setting may include pollen sterility, post-fertilization abortion of developing seeds due to high temperature, and reduced pollen viability under high-temperature and low-humidity conditions (El-Naby et al, 2011;Vijay et al, 2017).…”
Section: Treatment Effectsmentioning
confidence: 95%
“…The synchronization of pollination and fertilization time with hot air temperature, low humidity, and hot desiccating winds can severely reduce seed settings in Berseem clover, as reported in several studies (El-Naby et al, 2011;El-Naby et al, 2012). Factors contributing to low seed setting may include pollen sterility, post-fertilization abortion of developing seeds due to high temperature, and reduced pollen viability under high-temperature and low-humidity conditions (El-Naby et al, 2011;Vijay et al, 2017). The direct application of plant bio-regulators through foliar spray during pre-flowering stages might have been more effective in altering the life processes or structure of seed plants, improving seed yields, sizes, and quality, as reported by Nickell (1982).…”
Section: Treatment Effectsmentioning
confidence: 95%
“…As per our trial's findings, the last harvesting taken late resulted in a lower 1000-seed weight and yield, presumably owing to a shorter time available for seed setting under quickly hiking temperatures. Moreover, a rising air temperature coincides with low humidity, which results in a decline in pollination activity and fertilization rate [66][67][68][69][70]. Furthermore, lesser bee activity causes poor pollination, the infertility of pollen and seed development termination, leading to weak seed setting [63,65,71].…”
Section: Experiments 2 321 Yield Attributes and Seed Yieldmentioning
confidence: 99%